172 Role of the Sodium/Glutamate Blocker Riluzole in Enhancing Functional Outcomes in Patient Undergoing Surgery for Degenerative Cervical Myelopathy: Results of the Prospective, Multicenter Double-Blind Controlled CSM-Protect Randomized Controlled Trial. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Fehlings, Michael G; Kopjar, Branko; Ahn, Henry; Farhadi, Francis; Shaffrey, Christopher I; Nassr, Ahmad; Mummaneni, Praveen V; Arnold, Paul M; Jacobs, Bradley; Riew, K. Daniel; Brodke, Darrel S; Vaccaro, Alexander R; et al.
Abstract: INTRODUCTION: Degenerative cervical myelopathy (DCM), which encompasses cervical spondylotic myelopathy and ossification of the posterior longitudinal ligament, is the most common cause of spinal cord impairment. Decompressive surgery is the most effective treatment; however, most patients are left with residual neurological impairment and some experience neurological decline. Based on strong preclinical basic science evidence and collateral evidence from trials in human spinal cord injury and amyotrophic lateral sclerosis, we sought to explore if the sodium-glutamate antagonist riluzole would enhance neurological recovery and reduce perioperative neurological decline. METHODS: This is a phase III multicenter, double-blind, placebo-controlled, randomized controlled trial. Between March 2012 and June 2017, 300 surgically naive patients with moderate to severe DCM were enrolled at 16 sites. Subjects were randomized 1:1 to either the 50 mg riluzole bid or placebo-controlled group, beginning the medications at 14 d presurgery and ending at 28 d postoperative. Follow-up was at 6 and 12 mo to determine the primary endpoint, change in mJOA scores; and the secondary endpoints, change in SF-36v2, Neck Disability Index (NDI), Nurick grade, EQ-5D, American Spinal Injury Association motor and sensory scores, Bazaz scale, visual analog scale (VAS) for pain, grip strength, and neurological compilations. RESULTS: The average age was 57.9 yr (SD 10.2); 55.7% males; 80.1% white; 9.7% black. Baseline mJOA score was 11.84 (SD 1.5, range: 8-14); Nurick grade was 3.3 (SD 0.8); NDI 42.9 (SD 13.5); VAS arm/shoulder 4.7 (SD 2.9); VAS neck 4.9 (SD 3.0). The study will complete in December 2017 with a projected follow-up rate exceeding 90%. Efficacy results will be available and presented at the conference. CONCLUSION: This study contributes level I evidence concerning efficacy and safety of riluzole as an adjunct therapy to decompressive surgery for patients with DCM.